The mechanism of chronic intracellular infection with Brucella spp. - Guo, Xiaoyi; Zeng, Hui; Li, Mengjuan; Xiao, Yu; Gu, Guojing; Song, Zhenhui; Shuai, Xuehong; Guo, Jianhua; Huang, Qingzhou; Zhou, Bo; Chu, Yuefeng; Jiao, Hanwei (Frontiers in Cellular and Infection Microbiology, 2023)
Globally, brucellosis is a widespread zoonotic disease. It is prevalent in more than 170 countries and regions. It mostly damages an animal’s reproductive system and causes extreme economic losses to the animal husbandry industry. Once inside cells, Brucella resides in a vacuole, designated the BCV, which interacts with components of the endocytic and secretory pathways to ensure bacterial survival. Numerous studies conducted recently have revealed that Brucella’s ability to cause a chronic infection depends on how it interacts with the host. This paper describes the immune system, apoptosis, and metabolic control of host cells as part of the mechanism of Brucella survival in host cells. Brucella contributes to both the body’s non-specific and specific immunity during chronic infection, and it can aid in its survival by causing the body’s immune system to become suppressed. In addition, Brucella regulates apoptosis to avoid being detected by the host immune system. The BvrR/BvrS, VjbR, BlxR, and BPE123 proteins enable Brucella to fine-tune its metabolism while also ensuring its survival and replication and improving its ability to adapt to the intracellular environment.